Analysis of ICU admissions in a tertiary care setting - Poovathi, M.; Prasanna, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Management of the critically ill obstetric woman at an ICU is a unique challenge to ICU Physicians and obstetricians. Admission of obstetric patients occur approximately at 0.1-0.9% of the deliveries. The purpose of this study was to analysis of all critically ill obstetric patients admitted to a dedicated obstetric ICU to characterize the causes, clinical course, treatment any issues engendered by the presence of pregnant and postpartum women in a medical-surgical ICU. Methods: Details of all patients on the antepartum women or women less than six weeks postpartum admitted to the ICU from January 1, 2017 to December 31 ,2017 were reviewed. Obstetric data included gestational age at the time of admission and at delivery; type, indication, and location of delivery, and he ICU admitting diagnoses were categoried depending on the major system involved. Results: Out of a total of 10126 deliveries occurred in MGMGH, Trichy, in the past 1 year from January 2017 to December 2017 out of which the total number of ICU admissions were 141. The preclampsia/eclampsia related complications and Antepartum haemorrhage equally were responsible for the maximum number of obstetric ICU admissions and the number of ICU admissions for ventilator support and haemodynamic support were more.The leading cause of maternal death in the ICU admissions was pre-ecclampsia and eclampsia related complications .Ventilator support was required in 112 patients out of 141 ICU admissions , postpartum admissions were more than the antepartum admissions and nearly 73 of the ICU admissions were delivered by caesarean sections. Conclusions: The most common precipitants of ICU admission were obstetric hemorrhage and uncontrolled hypertension. Improved management strategies for these problems may signiﬁcantly reduce major maternal morbidity.